Online Da’wah and Social Media Misuse: Implications for Intra-Religious Peaceful Coexistence - Kazeem Oluwaseun DAUDA; Manzoor Apena Lawal (Dialogia, 2024)
The article examines the implications of social media misuse by Yoruba Muslim preachers (du’āt) on intra-religious peaceful coexistence. The research aims to highlight how the irresponsible use of online platforms by these preachers has led to increased hostility and division within the Muslim community. The study emphasizes the importance of adhering to Islamic principles that promote unity, tolerance, and mutual respect when conducting da’wah (religious outreach) online. To achieve this, the researchers used a descriptive survey design to analyze the social media activities of Yoruba, Nigeria du‘āt. The study reveals that some preachers have engaged in behavior contrary to Islamic teachings, such as spreading misinformation, hate speech, and engaging in personal attacks. This misuse of social media has caused polarization, mistrust, and even led to legal actions, further harming the peaceful coexistence of the Muslim community. The paper concludes that du‘āt must practice responsible and ethical online da‘wah that aligns with Islamic values, particularly those that foster harmony and peaceful coexistence. The research calls for a return to the core principles of Islamic law to mitigate the negative effects of social media misuse.